1997
DOI: 10.1094/phyto.1997.87.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Mycosphaerella fijiensis, Causal Agent of Black Sigatoka of Banana, to Propiconazole

Abstract: One hundred monoascosporic isolates of Mycosphaerella fijiensis were collected in February and November 1994 from each of two banana (Musa spp.) plantations in Costa Rica. Locations at San Pablo and Coopecariari had been sprayed with propiconazole for the past 7 years to control black Sigatoka. One hundred monoascosporic isolates from a third location, San Carlos, with no history of fungicide use, also were tested for sensitivity to propiconazole. Fifty percent effective concentration (EC(50)) values were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 13 publications
1
46
1
3
Order By: Relevance
“…The mean EC 50 value for tebuconazole (0.36 μg mL -1 ) was lower than the mean determined for isolates of M. fijiensis collected in the Ivory Coast (0.73 μg mL -1 ) (Koné et al, 2008). Comparing tebuconazole with other azoles routinely applied to control BLSD, the average EC 50 found in this study was higher than that found in a population of M. fijiensis in Costa Rica (0.06 μg mL -1 ) (Romero & Sutton, 1997). However, differences in methodological procedures do not allow for direct comparisons.…”
contrasting
confidence: 74%
See 1 more Smart Citation
“…The mean EC 50 value for tebuconazole (0.36 μg mL -1 ) was lower than the mean determined for isolates of M. fijiensis collected in the Ivory Coast (0.73 μg mL -1 ) (Koné et al, 2008). Comparing tebuconazole with other azoles routinely applied to control BLSD, the average EC 50 found in this study was higher than that found in a population of M. fijiensis in Costa Rica (0.06 μg mL -1 ) (Romero & Sutton, 1997). However, differences in methodological procedures do not allow for direct comparisons.…”
contrasting
confidence: 74%
“…The DMI fungicides inhibit the biosynthesis of sterol C-14 α-demethylation of 24-methylenedihydrolanosterol, a precursor of the cell membrane component ergosterol in fungi (Brent & Hollomon, 2007). Resistance to DMIs is also known and resistant isolates of M. fijiensis to propiconazole were reported (Romero & Sutton, 1997).…”
mentioning
confidence: 99%
“…Fungicide resistance to strobilurins has also been very fast in most banana-growing countries, and did not exceed 3 years' use in Costa Rica [38]. A significant shift in the sensitivity to DMI fungicides was also reported in Costa Rica after these fungicides had been used for more than 7 years [39]. After the emergence of resistance, first in a localized area, resistant strains progressively diffuse in most of the banana plantations of the same country [33,38].…”
Section: Blsd Causes Increasing Difficulties For Controlmentioning
confidence: 98%
“…The continuous use of a single product or products of the same chemical group promotes the onset of pathogen strains resistant to the fungicides used. The use of doses below the recommended dose also generates selection pressure favoring resistant pathogen strains, resulting in reduction of the effectiveness of fungicides, as found in Central America in the case of strobilurin (Marín et al, 2003) and propiconazole (Castro et al, 1995;Guzmán and Romero, 1997;Romero and Sutton, 1997).…”
Section: Introductionmentioning
confidence: 99%